ECONOMIC INTERACTION BETWEEN RUSSIAN FEDERATION AND REPUBLIC OF BURUNDI: STATE AND PROSPECTS - O. Konstantinova (Вестник университета)
Relations between the Russian Federation and the Republic of Burundi are traditionally friendly. Russia and Burundi have similar or identical political views. However, economic cooperation does not cover the whole range of possibilities. The article dedicates to the economic characteristics of the Republic of Burundi and resents its basic statistics. The state and prospects of economic cooperation between the Russian Federation and the Republic of Burundi are described. Conclusions about the feasibility of establishing a speedy process of mutually beneficial cooperation between the two countries have been done.